Racial/ethnic disparities in waitlisting for deceased donor kidney transplantation 1 year after implementation of the new national kidney allocation system. Issue 8 (18th April 2018) - Zhang, Xingyu; Melanson, Taylor A.; Plantinga, Laura C.; Basu, Mohua; Pastan, Stephen O.; Mohan, Sumit; Howard, David H.; Hockenberry, Jason M.; Garber, Michael D.; Patzer, Rachel E.
Abstract : The impact of a new national kidney allocation system (KAS) on access to the national deceased‐donor waiting list (waitlisting) and racial/ethnic disparities in waitlisting among US end‐stage renal disease (ESRD) patients is unknown. We examined waitlisting pre‐ and post‐KAS among incident (N = 1 253 100) and prevalent (N = 1 556 954) ESRD patients from the United States Renal Data System database (2005‐2015) using multivariable time‐dependent Cox and interrupted time‐series models. The adjusted waitlisting rate among incident patients was 9% lower post‐KAS (hazard ratio [HR]: 0.91; 95% confidence interval [CI], 0.90‐0.93), although preemptive waitlisting increased from 30.2% to 35.1% ( P  < .0001). The waitlisting decrease is largely due to a decline in inactively waitlisted patients. Pre‐KAS, blacks had a 19% lower waitlisting rate vs whites (HR: 0.81; 95% CI, 0.80‐0.82); following KAS, disparity declined to 12% (HR: 0.88; 95% CI, 0.85‐0.90). In adjusted time‐series analyses of prevalent patients, waitlisting rates declined by 3.45/10 000 per month post‐KAS ( P  <   .001), resulting in ≈146 fewer waitlisting events/month. Shorter dialysis vintage was associated with greater decreases in waitlisting post‐KAS ( P  < .001). Racial disparity reduction was due in part to a steeper decline in inactive waitlisting among minorities and a greater proportion of actively waitlisted minority patients. Waitlisting and racial disparity in waitlisting declined post‐KAS; however, disparity remains. Abstract : Following the 2014 change in the kidney allocation system, access to the national deceased donor waiting list declined among patients with less time on dialysis; overall racial disparity reduction was due primarily to a greater proportion of actively waitlisted patients.